An Egyptian case of isolated palmar lichen planus mimicking tinea nigra - Enas A.S Attia; Delram M Mahmoud (Wolters Kluwer Medknow Publications, 2020)
Exclusive palmoplantar lichen planus causes diagnostic challenge because of its rarity and the nonclassical morphology of the lesions. Herein, we report a case of exclusive palmar lichen planus resembling tinea nigra in an Egyptian male.